The SSG Wave Energy Converter: Performance, Status and Recent Developments - Mariano Buccino (Energies, 2012)
The Sea-wave Slot-cone Generator (SSG) is a Wave Energy Converter based on the wave overtopping principle; it employs several reservoirs placed on top of each other, in which the energy of incoming waves is stored as potential energy. Then, the captured water runs through turbines for electricity production. The system works under a wide spectrum of different wave conditions, giving a high overall efficiency. It can be suitable for shoreline and breakwater applications and presents particular advantages, such as sharing structure costs, availability of grid connection and recirculation of water inside the harbor, as the outlet of the turbines is on the rear part of the system. Recently, plans for the SSG pilot installations are in progress at the Svaaheia site (Norway), the port of Hanstholm (Denmark) and the port of Garibaldi (Oregon, USA). In the last-mentioned two projects, the Sea-wave Slot-cone Generator technology is integrated into the outer harbor breakwater and jetty reconstruction projects. In the last years extensive studies have been performed on the hydraulic and the structural response of this converter, with the aim of optimizing the design process. The investigations have been conducted by physical model tests and numerical simulations and many results have been published on both conference proceedings and journals. The main scope of this paper is reviewing the most significant findings, to provide the reader with an organic overview on the present status of knowledge.